Merosot Aura Kebangkitan Seni Politik: Sketsa Falsafat Walter Benjamin - Khudori Husnan (Himpunan Peminat Ilmu-Ilmu Ushuluddin (HIPIUS), 2013)
This article explains a thought of a philosopher, Walter Benjamin. His thought relates to the function of art that today changes i.e. just for fulfilling the political interests. The decreasing art, as mentioned, is particularly photography and film. As far as Benjamin is concerned, the photography and film that emerge as ‘art of politic’ are caused by Germany fascism, which has exploited those photography and film as its political vehicle. On the other hand, it is true that fascism succeeded to carry aesthetic into political stage. However, since fascism has authorized harshness and violence, as the result, such ‘political aesthetic’ is used for war.